Non-surgical management of knee osteoarthritis: comparison of ESCEO and OARSI 2019 guidelines - Arden, NK; Perry, TA; Bannuru, RR; Bruyère, O; Cooper, C; Haugen, IK; Hochberg, MC; McAlindon, TE; Mobasheri, A; Reginster, J-Y (Springer Nature, 2020)
Knee osteoarthritis (OA) is a heterogeneous disease associated with substantial effects on quality of life, and its clinical management is difficult. Among the several available guidelines for the management of knee OA, those from OARSI and ESCEO were updated in 2019. Here, we examine the similarities and differences between these two guidelines and provide a narrative to help guide health-care providers through the complexities of non-surgical management of knee OA. OARSI and ESCEO both recommend education, structured exercise and weight loss as core treatments, topical NSAIDs as first-line treatments and oral NSAIDs and intra-articular injections for persistent pain. Low-dose, short-term acetaminophen, pharmaceutical grade glucosamine and chondroitin sulfate are recommended by ESCEO whereas OARSI strongly recommends against their use (including all glucosamine and chondroitin formulations). Despite this difference, the two guidelines are consistent in the majority of their recommendations and provide useful treatment recommendations for individuals with OA and health-care providers.